Citizen science for water quality monitoring: Data implications of citizen perspectives. (15th September 2017) - Jollymore, Ashlee; Haines, Morgan J.; Satterfield, Terre; Johnson, Mark S.
Abstract: Citizen science, where citizens play an active role in the scientific process, is increasingly used to expand the reach and scope of scientific research while also achieving engagement and educational goals. Despite the emergence of studies exploring data outcomes of citizen science, the process and experience of engaging with citizens and citizen-lead groups through participatory science is less explored. This includes how citizen perspectives alter data outcomes, a critical upshot given prevalent mistrust of citizen versus scientist data. This study uses a citizen science campaign investigating watershed impacts on water quality to interrogate the nature and implications of citizen involvement in producing scientifically and societally relevant data. Data representing scientific outcomes are presented alongside a series of vignettes that offer context regarding how, why, and where citizens engaged with the project. From these vignettes, six specific lessons are examined towards understanding how integration of citizen participation alters data outcomes relative to 'professional' science. In particular, elements of participant social identity (e.g., their motivation for participation), and contextual knowledge (e.g., of the research program itself) can shape participation and resulting data outcomes. Such scientific outcomes are particularly relevant given continued concerns regarding the quality of citizen data, which could hinder scientific acceptance of citizen sciences. Importantly, the potential for meaningful engagement with citizen and participants within citizen groups - given significant capacity within the community - represents a substantial and under-realized opportunity. Graphical abstract: Highlights: Six lessons learned were derived from citizen science water quality monitoring. These center on how citizen perspectives can affect data outcomes. Perspectives includes motivations driving participation and citizen contextual knowledge. Divergences in citizens versus professional data critical in uptake of citizen science.